(untitled) (Journal of Architectural Design, 2023)
This article talks about its architecture and specific features based on the little-studied archival materials of the Mukhammad Naqibbek mosque, built in the 19th-20th centuries, located in the city of Kattakurgan, Samarkand region. Besides that, based on the analysis of the history of research related to this monument, relevant conclusions and recommendations are presented.